2022
DOI: 10.1101/2022.02.16.22270779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic analysis and prediction of genes associated with disorders on chromosome X

Abstract: Disease gene discovery on chromosome (chr) X is challenging owing to its unique modes of inheritance. We undertook a systematic analysis of human chrX genes. We observe a higher proportion of disorder-associated genes and an enrichment of genes involved in cognition, language, and seizures on chrX compared to autosomes. We analyze gene constraints, exon and promoter conservation, expression and paralogues, and report 127 genes sharing one or more attributes with known chrX disorder genes. Using a neural networ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…In the former category, LINKage-speci c-deubiquitylation-de ciency-induced embryonic defects (LINKED) syndrome, has been associated to pathogenic OTUD5 variants only in 2021,(31) whereas PDZD4 and ZMYM3 have been presently only proposed as a disease gene. (33,35) The microdeletion identi ed in ATRX (family 236) highlights the importance of searching for genomic rearrangements, exploiting exome data, or performing genome sequencing. In this case the deletion was missed by CMA due to lack of array probes in the deleted tract.…”
Section: Discussionmentioning
confidence: 99%
“…In the former category, LINKage-speci c-deubiquitylation-de ciency-induced embryonic defects (LINKED) syndrome, has been associated to pathogenic OTUD5 variants only in 2021,(31) whereas PDZD4 and ZMYM3 have been presently only proposed as a disease gene. (33,35) The microdeletion identi ed in ATRX (family 236) highlights the importance of searching for genomic rearrangements, exploiting exome data, or performing genome sequencing. In this case the deletion was missed by CMA due to lack of array probes in the deleted tract.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing only on the TM sites might not be enough for visualizing specific effect of drugs on TRPC4/5. Recent genetic study showed that R175C gain of function mutation in TRPC5 cause an impaired intellectual ability (Leitao et al, 2022). In this case, the drug affecting glutathionylation might improve said symptoms.…”
Section: Trpc4/5 Drug Discoverymentioning
confidence: 97%
“…The drugs made so far are concentrated in the membrane area. The GSSG glutathionylation site will be a good target considering the recent results showing the relation of TRPC5 R175C mutation and impaired intellectual ability (Leitao et al, 2022). It is also connected to zinc, which in turn connected to redox sensing and zinc poisoning.…”
Section: Trpc4/5 Drug Discoverymentioning
confidence: 99%
“…However, some of the X chromosome genes do escape from the described compensation system of inactivation leading to increased gene expression levels in females relative to males (Tukiainen et al, 2017). Since there is accumulating evidence on X chromosome genes being involved in mental function and the control of sex differences during brain development (Skuse, 2005), the escape of inactivation can contribute to sex differences in brain function, cognition and pathology (Leitão et al, 2022). In male mammals, on the other hand, there are genes located on the non-recombining region of the Y chromosome (NRY) that do not exist in females.…”
Section: Sexual Differentiation Of the Braingenetics And Hormonesmentioning
confidence: 99%